Bridging the GAAP : recent advances in finance and accounting - Venezia, Itzhak; Wiener, Zvi (World Scientific series in finance., 2012)
Bridging the GAAP: Recent Advances in Finance and Accounting lies at the intersection of the two disciplines. The readings in this volume bridge the gap between finance and accounting by looking at diverse topics in accounting and finance and by providing interesting points of view regarding their interface. Most of the chapters concentrate on the topic of fair value accounting and on the extent to which accounting numbers mirror the financial situation of the firm. This book combines new developments in the areas of theoretical and empirical finance and accounting, and emphasizes the convergence of these two disciplines to better serve researchers, investors and the general public. The papers contained in this volume will help scholars, practitioners and investors better understand the similarities and differences between these two important fields of study.